Sorghum as a Potential Valuable Aquafeed Ingredient: Nutritional Quality and Digestibility - Mohammad Zarei; Abdolsamad K. Amirkolaei; Jesse T. Trushenski; Wendy M. Sealey; Michael H. Schwarz; Reza Ovissipour (Agriculture, 2022)
The world population is increasing, and our current agricultural practices are not sustainable enough to address the concerns. Alternative proteins including plant-based proteins would provide a more sustainable source of food and feed ingredients. Among food systems, the aquaculture industry is rapidly growing, while still depending on marine sources as a main source of protein. Thus, using alternative plant-based proteins as a source for developing aquafeed would make this industry more viable. Sorghum is a valuable grain with high protein contents, proper mineral and fatty acids balance, and is available all around the world. However, sorghum has not been used widely for aquafeed development. In this review article, we cover sorghum production, composition, sorghum as a protein source for aquafeed development, and bioprocessing methods for enhancing the quality of sorghum.